2021
DOI: 10.1002/mar.21473
|View full text |Cite
|
Sign up to set email alerts
|

The effect of front‐of‐package nutrition labels on the choice of low sugar products

Abstract: Policy makers around the world are facing serious challenges in controlling citizens' obesity and healthiness, hence, they devote increased attention to the development of tools that communicate easily processable nutrition information. Front-ofpackage nutrition labels are one of such tools and have been used to signal the extent to which food items contain potentially unhealthy ingredients such as sugar or fat. In this research, we focus on sugar cues on three different food categories to investigate their im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 70 publications
2
23
0
Order By: Relevance
“…Therefore, appropriate labelling can be/become an adequate tool to implement and evaluate actions aimed at reducing sugar consumption [55]. The literature indicates that, with respect to the sugar content of foods, in addition to the commonly consumer-recognized means of labelling foods, other methods of labelling are also proposed to allow the consumer to better estimate or understand how much sugar is in a food product, e.g., indicating the amount of sugar in teaspoons, which, as a result, may contribute to the likelihood of purchasing decisions that are more rational from a health perspective [62].…”
Section: Information About Sugar On the Label In The Opinion Of The R...mentioning
confidence: 99%
“…Therefore, appropriate labelling can be/become an adequate tool to implement and evaluate actions aimed at reducing sugar consumption [55]. The literature indicates that, with respect to the sugar content of foods, in addition to the commonly consumer-recognized means of labelling foods, other methods of labelling are also proposed to allow the consumer to better estimate or understand how much sugar is in a food product, e.g., indicating the amount of sugar in teaspoons, which, as a result, may contribute to the likelihood of purchasing decisions that are more rational from a health perspective [62].…”
Section: Information About Sugar On the Label In The Opinion Of The R...mentioning
confidence: 99%
“…The difficulty associated with processing stimuli affects people's evaluations of those stimuli, as suggested by processing fluency theory (Alter & Oppenheimer, 2009; Oppenheimer, 2008; Reber & Unkelbach, 2010; Schwarz, 2004). For instance, prior research has shown that the difficulty associated with processing marketing stimuli such as advertising cues (Coulter & Suri, 2020), packaging (Mauri et al, 2021), fonts (Wu et al, 2021), and logos (Luffarelli, Mukesh, et al, 2019; Mahmood et al, 2019; Miceli et al, 2014) influences the attitudes and purchase intentions of consumers. We leverage this theory to predict how metaphors, which are cognitively demanding to process, influence product perceptions, choice, and adoption intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Two real-world 4-week RCTs used smartphone apps to enable study participants to scan product barcodes to receive interpretive or non-interpretive nutrition labels in Australia [ 30 ] and in New Zealand [ 31 ] and found no effect on healthiness of food purchases in any food category compared to control NIP condition. A recent online RCT with European adults aged 18 to 34 years found an interaction of food label and product category on probability of selecting low, medium, and high sugar products when comparing a traffic light label to pictures of numbers of teaspoons across smoothies, yoghurts and ready-meals categories [ 32 ]. This aligns with our study, where some labels improved the healthiness of choices in the beverage category but worsened the healthiness of yoghurt and breakfast cereal choices.…”
Section: Discussionmentioning
confidence: 99%